Online maps with APIs and WebServices - Peterson, Michael P. (Lecture Notes in Geoinformation and Cartography,, 2012)
The Internet has become the major form of map delivery. The current presentation of maps is based on the use of online services. This session examines developments related to online methods of map delivery, particularly Application Programmer Interfaces (APIs) and MapServices in general, including Google Maps API and similar services. Map mashups have had a major impact on how spatial information is presented. The advantage of using a major online mapping site is that the maps represent a common and recognizable representation of the world. Overlaying features on top of these maps provides a frame of reference for the map user. A particular advantage for thematic mapping is the ability to spatially reference thematic data.